Patient perception of interactive mobile healthcare apps: a predictive model. (25th November 2021) - Milner, Mattie; Winter, Scott; Mehta, Rian; Rice, Stephen; Pierce, Matthew; Anania, Emily; Candelaria-Oquendo, Karla; Garcia, Diego; Walters, Nathan
Many professionals connect with consumers through mobile app technology. It is no surprise that healthcare providers have explored this technology as a tool to reach patients. Despite increasing accessibility, willingness to use mobile technology, such as healthcare apps, can be affected by several different factors. This study aims to determine what factors predict a person's willingness to use this type of technology. Four hundred and five participants completed the study over two stages, including a hypothetical scenario using a mobile healthcare app and their willingness to use mobile healthcare applications. A backward stepwise regression analysis revealed two significant predictors: privacy concerns and likelihood to use the internet. Good model fit highlights the predictive power of the model on a new dataset. As technology becomes more prevalent, this research may help key stakeholder groups, such as healthcare providers, doctors, and patients, better understand patients' willingness to use mobile health applications.